The Effectiveness of Adjunctive Therapies Following Botulinum Toxin Type A Injections in Children with Cerebral Palsy - Tsegmid, Narantsetseg; Dorjbal, Delgerjargal; Erdenebileg, Nasantogtokh; Shirmen, Batchimeg; Zagd, Gerelmaa; Avirmed, Baljinnyam (Central Asian Journal of Medical Sciences, 2023)
Objectives: To investigate the effectiveness of intermittent vs. continuous adjunctive therapies following BoNT-A injections for children with cerebral palsy (CP). Methods: A quasi-experimental study was conducted with 80 participants with CP who received adjunctive therapies including physiotherapy and functional electrical stimulation after BoNT-A injections. The participants were randomly divided into two groups. In group A, half of the participants received intermittently adjunctive therapies. In group B, adjunctive therapies were organized continuously for another half. We measured changes in spasticity and dynamic spasticity used by the Modified Ashworth Scale and the Modified Tardieu Scale, and gross motor function used the Gross Motor Function Measure-88. Measurement of spasticity was carried out pre-injections and then 1- and 3-months post-injections. Measurement of gross motor function was organized pre- and post-injections. Results: The effectiveness of BoNT-A injections presented significant improvement in spasticity and gross motor function when it was combined with adjunctive therapies. The continuous adjunctive therapies had a greater reduction of spasticity. Both intermittent and continuous adjunctive therapies had a significant improvement in gross motor function. Conclusions: Our findings add to the evidence of the effectiveness of using different intervals of short-term adjunctive therapies for children with CP after BoNT-A injections.